2017
DOI: 10.1111/and.12854
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofTypha capensis(Rohrb.)N.E.Br. rhizome extract F1 fraction on cell viability, apoptosis induction and testosterone production in TM3-Leydig cells

Abstract: Typha capensis (Rohrb.)N.E.Br. (bulrush) is used by traditional healers in Southern Africa to treat male reproductive problems. This study aimed at investigating the effects of T. capensis on TM3-Leydig cells. T. capensis rhizome crude extract obtained from autumn, winter, spring and summer harvest was fractionated using HPLC into four fractions, and TM3-Leydig cells were incubated with different concentrations of the F1 fraction (0.01, 0.02, 0.1, 1, 10 and 100 μg/ml) for 24, 48 and 96 hr respectively. The fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition, the study on the effect of inositol only revealed histological results of sperm, which is insufficient to verify the effectiveness of the natural product [ 103 ]. Meanwhile, some experiments were conducted on normal cells or animals [ 17 , 40 , 42 , 45 , 76 , 104 , 170 ]. These results are insufficient to support whether the natural products have the capacity to protect genital damage or reverse reproductive disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study on the effect of inositol only revealed histological results of sperm, which is insufficient to verify the effectiveness of the natural product [ 103 ]. Meanwhile, some experiments were conducted on normal cells or animals [ 17 , 40 , 42 , 45 , 76 , 104 , 170 ]. These results are insufficient to support whether the natural products have the capacity to protect genital damage or reverse reproductive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…N.E.Br. belongs to the family of Typhaceae and is widely used for treating genital problems, male potency, and blood circulation [ 45 ]. Its root extract, treated with doses of 10 and 100 μg/mL for 96 h, improved testosterone production and marked significant difference in DNA fragmentation in TM3-leydig cells.…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…Several studies had previously established that TM3 cells are suitable for use in the determination of testosterone production (Ilfergane & Henkel, 2018; Jambor et al., 2019; Lin et al., 2019; Liu et al., 2016; Xia et al., 2020). However, another study demonstrated that unstimulated and stimulated TM3 cells produced a low amount of testosterone and a high amount of progesterone, suggesting that TM3 cells are unsuitable for studying the gonadal androgen biosynthesis due to altered steroidogenic pathways (Engeli, Fürstenberger, Kratschmar, & Odermatt, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The early apoptotic events by means of Annexin V-Cy3 (AnnCy3) binding to TM3 cells was determined in a study (31). The result revealed that the rhizome extract F1 fraction of T. capensis showed no cytotoxic effects including cell viability, induction of apoptosis and DNA fragmentation at concentrations used in the study.…”
Section: Cytotoxic Effectsmentioning
confidence: 98%
“…Another study investigated the effects of rhizome extract F1 fraction of T. capensis obtained during autumn, winter, spring and summer harvests on TM3-Leydig cells at different concentrations of 0.01, 0.02, 0.1, 1, 10 and 100 μg / mL for 24, 48 and 96 hrs (31). After 48 h of exposure, F1 fraction of all four seasons strongly increased the production of testosterone in TM3 cells with maximal impact at 0.1 μg/mL, in a dose-dependent manner.…”
Section: Fertility-promoting Effectmentioning
confidence: 99%